Incentive Effects of Terminations: Applications to the Credit and Labor Markets - Stiglitz, Joseph E.; Weiss, Andrew (American Economic Review, 1983)
Stiglitz and Weiss examine the incentive effects of terminations in terms of applications to the credit and labor markets.